Connected on campus for dummies (Wiley Pub., 2006)
Laptop or desktop? Wired or wireless? Is there a PDA in your future? Here's what you should know to choose the right technology for college, set up and secure your system, make the most of online research, e-mail in your assignments, and even take tests online. Find the essentials of a graphing calculator, the latest on wireless hotspots, and top troubleshooting tips right here!